2018
DOI: 10.1074/jbc.ra117.000567
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule targeting of the STAT5/6 Src homology 2 (SH2) domains to inhibit allergic airway disease

Abstract: Asthma is a chronic inflammatory disease of the lungs and airways and one of the most burdensome of all chronic maladies. Previous studies have established that expression of experimental and human asthma requires the IL-4/IL-13/IL-4 receptor α (IL-4Rα) signaling pathway, which activates the transcription factor STAT6. However, no small molecules targeting this important pathway are currently in clinical development. To this end, using a preclinical asthma model, we sought to develop and test a small-molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The former SH domains are considered associating with proteins of signaling pathways involving in the cytoskeleton, the Ras associated protein, and many others. [11] The CLK2 kinase has shown to interact with serine/arginine-rich (SR) proteins of the spliceosomal complex, which is responsible for the SR proteins to control RNA splicing. [12] This protein kinase is involved in the regulation of several cellular processes and may serve as a link between cell cycle progression, apoptosis, and telomere length regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The former SH domains are considered associating with proteins of signaling pathways involving in the cytoskeleton, the Ras associated protein, and many others. [11] The CLK2 kinase has shown to interact with serine/arginine-rich (SR) proteins of the spliceosomal complex, which is responsible for the SR proteins to control RNA splicing. [12] This protein kinase is involved in the regulation of several cellular processes and may serve as a link between cell cycle progression, apoptosis, and telomere length regulation.…”
Section: Discussionmentioning
confidence: 99%
“…A critical task suggested by our analyses is determining the essential inflammatory pathways that drive eosinophilic inflammation of both the upper and lower airways during airway mycosis. STAT6 has previously been shown to drive eosinophilic lower airway inflammation under a variety of short-term inflammatory challenge conditions, including fungal ( 10 ). Utilizing STAT6-deficient mice, we found that challenge of mice with A. niger over 12 weeks resulted in a similarly marked reduction in lung eosinophils as assessed by flow cytometry, but we also found near-complete suppression of all other inflammatory cells including macrophages, neutrophils, and T cells ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…The STAT6 inhibitor is formulated in liposomes with 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC; 850335, Avanti Polar Lipids) as previously described ( 10 ). Prior to formulating daily treatments, vehicle and drug suspensions were briefly sonicated for 30 s and vortexed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations